Innovation in Banking and Excessive Loan Growth. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The volume of credit extended by a bank can be an informative signal of its abilities in loan selection and management. It is shown that, under asymmetric information, banks may therefore rationally lend more than they would otherwise in order to demonstrate their quality, thus negatively affecting financial system soundness. Small shifts in technology and uncertainty associated with new technology may lead to large jumps in equilibrium outcomes. Prudential measures and supervision are therefore warranted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet